2018
DOI: 10.1016/j.jtcvs.2018.01.084
|View full text |Cite
|
Sign up to set email alerts
|

Rapid deployment or sutureless versus conventional bioprosthetic aortic valve replacement: A meta-analysis

Abstract: RDAVR is associated with significantly shorter ACC and CPB times than CAVR, although this difference did not translate into improved postoperative outcomes, early mortality, and all-cause mortality during follow-up. Care might be needed when implanting RD valves because they are associated with a higher incidence of PPM insertion, regardless of the RD valve type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 44 publications
6
32
1
Order By: Relevance
“…Ghoneim and colleagues studied the outcomes of various biological valve options, including stentless valves, stented valves and SU-AVR, and reported similar postoperative transvalvular gradient in the SU-AVR group compared with the stented group 34. The similarity in postoperative transvalvular gradient between SU-AVR and conventional biological valves was also reported in a meta-analysis by Sohn and colleagues 21. More data from randomised trials will be required in order to determine if SU-AVR prostheses truly have superior haemodynamics when compared with conventional valves.…”
Section: Specific Indications For Sutureless Valvesmentioning
confidence: 70%
See 1 more Smart Citation
“…Ghoneim and colleagues studied the outcomes of various biological valve options, including stentless valves, stented valves and SU-AVR, and reported similar postoperative transvalvular gradient in the SU-AVR group compared with the stented group 34. The similarity in postoperative transvalvular gradient between SU-AVR and conventional biological valves was also reported in a meta-analysis by Sohn and colleagues 21. More data from randomised trials will be required in order to determine if SU-AVR prostheses truly have superior haemodynamics when compared with conventional valves.…”
Section: Specific Indications For Sutureless Valvesmentioning
confidence: 70%
“…In a recent meta-analysis by Sohn and colleagues which compared SU-AVR with conventional bioprosthetic valves, there was a significant reduction in CCT and CPB times in SU-AVR patients21 (table 1). However, the investigators concluded that these reductions did not translate into improvements in perioperative outcomes, in particular early mortality.…”
Section: Sutureless Valves Versus Conventional Avrmentioning
confidence: 98%
“…Due to the design of sutureless valves, their implantation in AVR is positioned below the aortic annulus, which increases the risk of atrioventricular block . On the other hand, PVL is suspected to be an adverse outcome as a result of inadequate positioning and sizing of sutureless valves or incomplete annulus decalcification . In recent years, two case reports from the literature have reported valve perforation following the use of Cor‐Knot device, leading to valvular regurgitation .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the use of Cor‐Knot in heart valve surgery is not associated with postoperative complications including the risk of PPI and PVL . In contrast, recent meta‐analyses have reported that sutureless technology is associated with increased risk of PPI and PVL . Sutureless valve is an alternative surgical adjunct that replaces the conventional prosthetic valve and boasts its reduced need for sutures, thereby minimizing CPB and AXT .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid deployment valves have reduced cross‐clamp and bypass times with excellent 1‐year performance 9 . While the use of rapid deployment valves for aortic valve replacement has not been shown to be superior to conventional bioprosthetic valves, 10 there are scenarios where it is favorable, such as a calcified aortic root 11 …”
Section: Commentsmentioning
confidence: 99%